HADS-depression score is a mediator for illness perception and daily life impairment in Takayasu's arteritis - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (SPRINGER LONDON LTD, 2021)
Introduction/objectives The aim of this study was to evaluate the relationships among the disease activity, illness perception, daily life performance, anxiety and depression status as potential mediators in Takayasu's arteritis (TAK) patients. Method In this cross-sectional study, 77 TAK patients were included. Data were collected by a clinical examination and a structured questionnaire regarding patient reported outcome measures (PROMs). Indian Takayasu's Arteritis Activity Score2010 (ITAS2010) was used to assess the disease activity (0: inactive vs >= 1: active). Illness Perception Questionnaire-Revise (IPQ-R), Work Productivity and Activity Impairment (WPAI) and Hospital Anxiety and Depression Scale (HADS) as PROMs were used to understand for the patient' perspective. After preliminary analysis, complex relationships among these variables were evaluated by mediation analyses in the study. Results WPAI-Daily impairment score, HADS-A and HADS-D scores as well as IPQ-R Consequence score were found be high in active TAK patients (p = 0.008; p = 0.001; p = 0.031; p = 0.001). HADS-D score was also correlated with WPAI-Daily impairment score and IPQ-R Consequence score (p < 0.05). In mediation analysis, IPQ-R Consequence score was directly mediated by disease activity (ITAS2010) (p = 0.0173) and indirectly mediated through HADS-D score (p = 0.0003). Similarly, HADS-D score was associated with poor WPAI-Daily impairment score in the mediation analysis in the indirect path (p = 0.0069). Disease activity (ITAS2010) also increased WPAI-Daily impairment score in direct path (p = 0.043). Conclusions Active TAK patients perceived their illness more seriously and experienced more impairment in their daily life. Depression status as the mediator influenced them poorly. These interactions could give clues to improve PROMs in the clinical practice.
Keywords: Activity; Depression; Direct effects; Indirect effects; Mediation analysis; Takayasu; Takayasu arteritis